A review of Hybalus Dejean from Tunisia (Coleoptera: Scarabaeidae: Orphninae) with description of a new species - Frolov, Andrey; Akhmetova, Lilia; Montreuil, Olivier (Zootaxa, 2019)
The scarab beetles of the subfamily Orphninae Erichson are the most diverse in the tropics (Paulian 1948; Frolov 2012). Yet there are two genera occurring in the Palearctic Region, Hybalus Dejean, 1833 and Chaetonyx Schaum, 1862. Of them, the former is rather speciose and comprises 37 species distributed mostly in the Atlas Mountains of North Africa (Baraud 1991; López-Colón 2006; López Colón & Bahillo de la Puebla 2014; Bezděk 2016). Adult Hybalus are all apterous and most of the species have rather restricted ranges or are known from single localities. The beetles are similar externally and only a few species have distinctive features of the head or anterior legs in males; the most important and, in majority of species, the only reliable character to differentiate species is the shape of the parameres (Petrovitz 1964; Baraud 1991).